The Influence of Halal Knowledge, Islamic Religiosity, and Attitude on Halal Purchase Decisions Moderated by Purchase Intention Among Generation Z - Handi Risza; Sudarmawan Sudarmawan; Arif Haryadi (Greenation Research & Yayasan Global Resarch National, 2026)
Research Originality: This research provides a novel perspective by positioning purchase intention as a moderating variable in halal consumer behaviour, contributing to the growing literature on Islamic marketing and behavioural decision-making. The rapid growth of the halal industry has transformed halal products from a purely religious necessity into a global lifestyle phenomenon. Generation Z, characterized by high digital literacy and strong social media exposure, represents a strategic segment in the halal market. Research Objective: This study aims to analyse the influence of halal knowledge, Islamic religiosity, and attitude on halal purchase decisions among Generation Z consumers, while examining the moderating role of purchase intention in strengthening the relationships between these variables. Research Method: This research explores how halal knowledge, Islamic religiosity, and consumer attitudes influence purchasing decisions for halal products, while examining the moderating role of purchase intention among Generation Z. A survey-based quantitative method was applied, involving 300 Muslim respondents aged between 17 and 27 in Indonesia. Data analysis was conducted using SEM-PLS. Result: The findings demonstrate that all three antecedent variables—knowledge, religiosity, and attitude—significantly affect purchasing decisions. Moreover, purchase intention strengthens the impact of these variables, acting as a critical link between internal motivations and actual behaviour. Among the predictors, religiosity exerts the strongest influence. These results indicate that although cognitive understanding and positive perceptions are important, behavioural intention plays a decisive role in shaping real purchasing actions. This study enriches consumer behaviour literature by integrating moderating effects into the TPB framework and offers strategic insights for halal market stakeholders targeting younger consumers. Implication: This study contributes to the extension of the Theory of Planned Behaviour (TPB) by incorporating moderating effects and provides practical insights for halal industry stakeholders targeting Generation Z.